A recent perspective on fiber and hexon genes proteins analyses of fowl adenovirus toward virus infectivity—A review - Mohamed Sohaimi, Norfitriah; Bejo, Mohd. Hair (National Authority for Scientific Research Faculty of Veterinary Medicine Tripoli University, 2021)
Fowl adenovirus (FAdV) is a double-stranded DNA virus with a non-enveloped structure comprising three major proteins known as hexon, penton, and fiber. Molecular analysis which emphasizes on hexon and fiber proteins is currently the major focus of curiosity for FAdV antigenicity and pathogenicity. Recently, disease outbreaks associated with FAdV infections such as inclusion body hepatitis, hepatitis hydropericardium syndrome, and gizzard erosion, were commonly reported and continue to increase worldwide. Studies on the virulence gene of the virus were intensively conducted to provide a better understanding on the role of these major capsid proteins in the development of a safe and effective vaccine against the disease in the poultry industry. This paper highlights the variations of the fiber and hexon genes, their importance in genotypes and serotypes differentiation, and infectivity between FAdV strains. It appears that the L1 loop of hexon and the knob of fiber genes are the infectivity markers for FAdV infection. The fiber-2 protein plays a major role in FAdV pathogenicity than the hexon protein, while the fiber-1 protein is important for viral replication and assembly, regardless of virulence capability instead of infectivity. The hexon protein plays a major role in virus infectivity and tissue tropism. These findings could further enhance the knowledge of FAdV strains’ classification and evolution, diagnosis, and strategies to prevent and control FAdV infection and outbreaks in chicken farms.